Emotional Pain Mediates the Link Between Preoccupied Attachment and Non-suicidal Self-Injury in High Suicide Risk Psychiatric Inpatients - Molaie, Ali M.; Chiu, Chih-Yun; Habib, Zara; Galynker, Igor; Briggs, Jessica; Rosenfield, Paul J.; Calati, Raffaella; Yaseen, Zimri S. (Frontiers in Psychology, 2019)
Background: Non-suicidal self-injury (NSSI) is a risk factor for suicide attempts (SA). Both attachment disturbances and cognitive and emotional problems (e.g., emotional pain) have been associated with SA history. This study sought to determine differential contributions of attachment styles and cognitive and emotional states associated with SA to lifetime NSSI occurrence among adults hospitalized for suicide risk. Sampling and Methods: Adult psychiatric inpatients (n = 200) were assessed for attachment style, cognitive and emotional states, and lifetime NSSI within 72 hours of hospitalization. Binary logistic regression and mediation analyses were performed. Results: Preoccupied attachment and emotional pain at admission were independently associated with lifetime NSSI. Emotional pain partially mediated the relationship between preoccupied attachment and lifetime NSSI. Limitations: The cross-sectional nature of the study and the use of a dichotomous (yes/no) measure of NSSI, not specifically designed for its assessment. Conclusions: Preoccupied attachment and emotional pain are associated with NSSI and may be useful targets for assessing risk of NSSI.